Peroxisome proliferator‐activated receptor gamma blunts endothelin‐1‐mediated contraction of the uterine artery in a murine model of high‐altitude pregnancy. Issue 3 (23rd January 2020) - Lane, Sydney L.; Doyle, Alexandrea S.; Bales, Elise S.; Houck, Julie A.; Lorca, Ramón A.; Moore, Lorna G.; Julian, Colleen G.
Abstract: The environmental hypoxia of high altitude (HA) increases the incidence of intrauterine growth restriction (IUGR) approximately threefold. The peroxisome proliferator‐activated receptor γ (PPAR‐γ), a ligand‐activated nuclear receptor that promotes vasorelaxation by increasing nitric oxide and downregulating endothelin‐1 (ET‐1) production, has been implicated in IUGR. Based on our prior work indicating that pharmacologic activation of the PPARγ pathway protects against hypoxia‐associated IUGR, we used an experimental murine model to determine whether such effects may be attributed to vasodilatory effects in the uteroplacental circulation. Using wire myography, ex vivo vasoreactivity studies were conducted in uterine arteries (UtA) isolated from pregnant mice exposed to hypoxia or normoxia from gestational day 14.5 to 18.5. Exposure to troglitazone, a high‐affinity PPARγ agonist‐induced vasorelaxation in UtA preconstricted with phenylephrine, with HA‐UtA showing increased sensitivity. Troglitazone blunted ET‐1‐induced contraction of UtA in hypoxic and normoxic dams equivalently. Immunohistological analysis revealed enhanced staining for ET‐1 receptors in the placental labyrinthine zone in hypoxic compared to normoxic dams. Our results suggest that pharmacologic PPAR‐γ activation, via its vasoactive properties, may protect the fetal growth under hypoxic conditions by improving uteroplacental perfusion and thereby justify further investigation into PPARγ as a therapeutic target for IUGR in pregnancies complicated by hypoxia.